2019
DOI: 10.1007/s11661-019-05381-z
|View full text |Cite|
|
Sign up to set email alerts
|

Advancement in the Pressureless Sintering of CP Titanium Using High-Frequency Induction Heating

Abstract: High-frequency induction heating is applied as an alternative heating source for pressureless sintering of commercially pure Ti powders, aiming to intensify the sintering process. The effects of the process parameters on the properties of the sintered material are systematically studied. The initial powder compact density is the most influential parameter permitting sintered structures with highly porous to almost fully dense appearance. Short heating time combined with sintering to temperatures just above the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Figure 2 shows the results of the microstructural analysis performed on the Ti–xMn–xNb alloys. Regardless of the chemical composition, a small amount of residual porosity is present in the microstructure, which is typical for powder metallurgy Ti alloys 27 , 28 . The majority of the pores are isolated, they have either spherical or elongated morphology, they are primarily located at the boundaries between phases, and their volumetric fraction slightly increases with the amount of alloying elements added.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the results of the microstructural analysis performed on the Ti–xMn–xNb alloys. Regardless of the chemical composition, a small amount of residual porosity is present in the microstructure, which is typical for powder metallurgy Ti alloys 27 , 28 . The majority of the pores are isolated, they have either spherical or elongated morphology, they are primarily located at the boundaries between phases, and their volumetric fraction slightly increases with the amount of alloying elements added.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, further induction sintering provides similar densification results compared to furnace sintering, [33] but in a significantly shorter time. Raynova et al [34] studied the impact of the green density on densification during induction sintering. It has been revealed that with increasing green compact density, the increment of the density during sintering decreased significantly.…”
Section: A Effect Of Initial Materials and Sintering Conditions On Thmentioning
confidence: 99%
“…Similar values were previously reported for induction sintering of commercially pure (CP) titanium powder or mixtures of elemental powders based on titanium consolidated in comparable conditions. [11,25,34]…”
Section: A Effect Of Initial Materials and Sintering Conditions On Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid-state sintering of powder compacts results from the reduced surface energy of particles in close proximity, whereby mass transport diffusion takes place, with the most common approach performed through solid-state furnace sintering [ 35 ]. Other highly effective routes have been developed more recently, such as microwave sintering [ 36 , 37 ], Spark Plasma Sintering (SPS) or Field-Assisted Sintering (FAST) [ 38 ], or via direct [ 39 , 40 , 41 ] or indirect [ 42 , 43 ] induction. An advantage of microwave, SPS/FAST, and induction sintering, in contrast to conventional sintering, is the capability to sinter in only a few minutes rather than hours or days [ 36 , 38 , 41 ].…”
Section: Introductionmentioning
confidence: 99%